Telemedicine in the ICU: clinical outcomes, economic aspects, and trainee education. Issue 2 (April 2019) - Becker, Christian D.; Fusaro, Mario V.; Scurlock, Corey
Abstract : Purpose of review: The evidence base for telemedicine in the ICU (tele-ICU) is rapidly expanding. The last 2 years have seen important additions to our understanding of when, where, and how telemedicine in the ICU adds value. Recent findings: Recent publications and a recent meta-analysis confirm that tele-ICU improves core clinical outcomes for ICU patients. Recent evidence further demonstrates that comprehensive tele-ICU programs have the potential to quickly recuperate their implementation and operational costs and significantly increase case volumes and direct contribution margins particularly if additional logistics and care standardization functions are embedded to optimize ICU bed utilization and reduce complications. Even though the adoption of tele-ICU is increasing and the vast majority of today's medical graduates will regularly use some form of telemedicine and/or tele-ICU, telemedicine modules have not consistently found their way into educational curricula yet. Tele-ICU can be used very effectively to standardize supervision of medical trainees in bedside procedures or point-of-care ultrasound exams, especially during off-hours. Lastly, tele-ICUs routinely generate rich operational data, as well as risk-adjusted acuity and outcome data across the spectrum of critically ill patients, which can be utilized to support important clinical research and quality improvement projects. Summary: The value of tele-ICU to improve patient outcomes, optimize ICU bed utilization, increase financial performance and enhance educational opportunities for the next generation of providers has become more evident and differentiated in the last 2 years.